Aktualisering av legenden om St. Sunniva og øyen Selja: Mellom diktning og historie - Selberg, Torunn (Tidsskrift for kulturforskning, 2018)
This article discusses actualizations of the legend about St. Sunniva, one of three Norwegian saints. After a silence for several hundreds of years, this legend is today being revitalized in various ways, in materializations like monuments and pictures, as festivals, in songs and poetry, as part of a Norwegian pilgrimage renaissance. The legend tells about an Irish princess, escaping a heathen Viking suitor in a boat without oars and sails, landing on the small island of Selja on the North-west coast of Norway where she died a martyr. The Viking king Olav Tryggvason made the island a pilgrimage destination, and so it continued to be during medieval times, and is today being revitalized in the re-telling of the narrative about Sunniva. This article discusses how and why a medieval legend is being revitalized to-day, what contemporary trends and ideas does the legend talks to, and how are they expressed in the contemporary retelling of the legend.